Publitsistika in Creative Work of I.A. Bunin - A. A. Dyakina (Научный диалог, 2021)
The article discusses the issue of refraction of the categories “publitsistika” (publicism) and “publitsistichnost” (with the elements of publicism) in the work of I. A. Bunin. It is shown that the definition of “publitsistika” in the categorical sense is applicable, first of all, to his works of the period of emigration, which are of a socio-political nature. Particular attention is paid to the origins of literary-critical and memoir publitsistika, outlined in Bunin’s early articles and essays, in which signs of “publitsistichnost” are found, expanding the boundaries of the declared topic to the level of social problems. The author dwells on certain features characteristic of the future publiсistic manner of the writer: a tendency to polemics, a straightforward position, open attacks towards opponents, the use of artistry. The relevance of the study is due to the need to consider early literary critical articles, essays by Bunin, his «Speeches on the anniversary of the newspaper “Russkie vedomosti”» and publiсistic of the mature period as an integral creative process that has its own dynamics. The novelty of the research is seen in the proposed approach to considering the specifics of the writer’s publicistic heritage, which consists in a systemic and holistic understanding, the involvement of integrative humanitarian knowledge as a context and comments. It is proposed to use mathematical and informational research methods approved by the author in the textual analysis of Bunin’s publicistic works.